The International Carbon Credit Market: A Comparative Study Between the Regulated and Voluntary Markets the Period 2004 to 2011 - Souza, André Luis (2012)
The general objective of this research is to investigate the main differences between the regulated and voluntary carbon markets in Brazil, over the period from 2004 to 2011.  In order to achieve the proposed objective, we conducted exploratory bibliographic research, which contributed to an understanding of the object investigated, as well as documental research, which utilized content analysis techniques to collect secondary data obtained from Project Design Documents (PDDs).  This data was mapped and extracted from the websites and databases we visited, which enabled the collection of quantitative and qualitative data.  Furthermore, we mapped voluntary carbon market projects through a search of the databases and institutional websites of International Standards and their applicants, while projects from the regulated carbon market were extracted from the existing databases of the Ministry of Science and Technology (Ministério da Ciência e Tecnologia: MCT).  We verified differences and similarities between the regulated and voluntary carbon markets in Brazil up to that point in time, according to which the former had 499, while the latter had 111.  We identified that the main differences between the regulated and carbon markets in Brazil are in their sectoral scopes.